2019
DOI: 10.1029/2018gl081724
|View full text |Cite
|
Sign up to set email alerts
|

Global Ensemble Forecast System (GEFS) Predictions of Days 1–15 U.S. Tornado and Hail Frequencies

Abstract: U.S. severe convective storms have grown to represent a 10 billion dollar annual peril for the insurance industry, and their accurate prediction remains a challenging task. This study examines days 1–15 severe convective storm predictions from the Global Ensemble Forecast System (GEFS). GEFS forecasts are based on the Supercell Composite Parameter and verified against spatially smoothed tornado and hail reports over the periods 1 March to 31 May 2016–2017. Skill is analyzed for deterministic forecasts (ensembl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…ERTAF began in spring 2015 motivated by the realization that patterns favorable for severe weather can sometimes be predicted at extended lead times (7+ days), beyond the typical range at which numerical weather prediction (NWP) models have useful skill at predicting atmospheric ingredients favorable for tornadoes (Gensini & Tippett, ; Zhang et al, ). These occasional forecasts of opportunity are made possible by catching the emergence of coherent subseasonal signals within the GSDM framework and using the time scales typical of these processes to anticipate the development of regional circulation anomalies favorable for tornadoes, such as those that developed in May 2019.…”
Section: Resultsmentioning
confidence: 99%
“…ERTAF began in spring 2015 motivated by the realization that patterns favorable for severe weather can sometimes be predicted at extended lead times (7+ days), beyond the typical range at which numerical weather prediction (NWP) models have useful skill at predicting atmospheric ingredients favorable for tornadoes (Gensini & Tippett, ; Zhang et al, ). These occasional forecasts of opportunity are made possible by catching the emergence of coherent subseasonal signals within the GSDM framework and using the time scales typical of these processes to anticipate the development of regional circulation anomalies favorable for tornadoes, such as those that developed in May 2019.…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly true for severe convective storms (SCSs; defined as thunderstorms that produce tornadoes, large hail, and/or damaging convective wind gusts) given the significant impacts on various economic and societal sectors (Simmons and Sutter 2013;Smith and Matthews 2015;NCEI 2019). Recent research has shown skill in forecasting U.S. tornado and hail frequency at various lead times in the subseasonal period (Allen et al 2015;Lepore et al 2017;Baggett et al 2018;Lepore et al 2018;Gensini and Tippett 2019), including a recently documented operational forecast of an anomalously high period of tornado frequency in late May 2019 issued more than three weeks in advance (Gensini et al 2019).…”
mentioning
confidence: 99%
“…The Madden-Julian oscillation (MJO) and the global wind oscillation (GWO) are two such modes of atmospheric variability with documented periodicity on the subseasonal time scale (Weickmann and Berry 2009;Zhang 2013). While not mutually exclusive (the GWO encompasses the MJO through incorporation of the tropical zonal wind fields), both processes have been shown to modulate tornado and hail frequency across the United States (Barrett and Gensini 2013;Thompson and Roundy 2013;Barrett and Henley 2015;Gensini and Marinaro 2016;Baggett et al 2018;Gensini and Allen 2018;Tippett 2018;Moore 2018;Gensini et al 2019;Moore and McGuire 2019). A known physical pathway by which the MJO and GWO influence CONUS severe weather is by generating positive mountain and frictional torques, particularly as convection associated with the MJO increases across the Maritime Continent and moves toward the international date line.…”
mentioning
confidence: 99%
See 2 more Smart Citations